Compassion fatigue: A meta-narrative review of the healthcare literature. (April 2017) - Sinclair, Shane; Raffin-Bouchal, Shelley; Venturato, Lorraine; Mijovic-Kondejewski, Jane; Smith-MacDonald, Lorraine
Abstract: Background: Compassion fatigue describes a work-related stress response in healthcare providers that is considered a 'cost of caring' and a key contributor to the loss of compassion in healthcare. Objective: The purpose of this review was to critically examine the construct of compassion fatigue and to determine if it is an accurate descriptor of work-related stress in healthcare providers and a valid target variable for intervention. Design: Meta-narrative review. Data Sources: PubMed, Medline, CINAHL, PsycINFO, and Web of Science databases, Google Scholar, the grey literature, and manual searches of bibliographies. Review methods: Seminal articles and theoretical and empirical studies on compassion fatigue in the healthcare literature were identified and appraised for their validity and relevance to our review. Sources were mapped according to the following criteria: 1) definitions; 2) conceptual analyses; 3) signs and symptoms; 4) measures; 5) prevalence and associated risk factors; and 6) interventions. A narrative account of included studies that critically examines the concept of compassion fatigue in healthcare was employed, and recommendations for practice, policy and further research were made. Results: 90 studies from the nursing literature and healthcare in general were included in the review. Findings emphasized that the physical, emotional, social and spiritual health of healthcare providers is impaired by cumulative stress related to their work, which can impact the delivery of healthcare services; however, the precise nature of compassion fatigue and that it is predicated on the provision of compassionate care is associated with significant limitations. The conceptualization of compassion fatigue was expropriated from crisis counseling and psychotherapy and focuses on limited facets of compassion. Empirical studies primarily measure compassion fatigue using the Professional Quality of Life Scale, which does not assess any of the elements of compassion. Reported risk factors for compassion fatigue include job-related factors, fewer healthcare qualifications and less years experience; however, there is no research demonstrating that exemplary compassionate carers are more susceptible to 'compassion fatigue'. Conclusion: In the last two decades, compassion fatigue has become a contemporary and iconic euphemism that should be critically reexamined in favour of a new discourse on healthcare provider work-related stress.